Pengaruh Manajemen Bimbingan Konseling terhadap Disiplin Peserta Didik Kelas XI di SMK Negeri 1 Siatas Barita Tahun Pembelajaran 2023/2024 - Lisna Panggabean; Rogate Artaida Tiarasi Gultom (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to determine the positive and significant influence of guidance and counseling management on the discipline of class XI students at SMK Negeri 1 Siatas Barita. The method used in this research is a quantitative research method. The population is the total number of students in class XI of SMK Negeri 1 Siatas Barita, totaling 426 people and a sample of 65 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 30 items. The results of the data analysis show that there is a positive and significant influence between guidance and counseling management on the discipline of class The positive value obtained is rxy = 0.585 > =0.05,dk=n-2=63)= 2,000, thus there is a significant relationship between variable 0.786. b) Regression coefficient of determination test (r2) = 34.3%. 3) Test the hypothesis using the F test to obtain Fcounta=0.05,n=65) = 0.244, thus it is known that there is a positive influence between variable artable( > Ftable, namely 32.845 > 4.00. Thus Ha is accepted and H0 is rejected.